A case report of hepatitis B virus reactivation 19 months after cessation of chemotherapy with rituximab - Guo, Xiangjuan; Ji, Tongtong; Xin, Shengliang; Xu, Jinghang; Yu, Yanyan (Frontiers in Immunology, 2022)
A 72-year-old woman presented to our hospital with elevation of serum transaminases. Her blood tests showed the hepatitis B surface antigen (HBsAg) and hepatitis B e antigen (HBeAg) negative. Rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) were given for the diffuse large B-cell lymphoma. She didn’t receive anti- hepatitis B virus (HBV) drug for the isolated HBcAb positive. HBV reactivation confirmed based on the serum HBV DNA detectable until 19 months after stopping R-CHOP regimen. HBV DNA became undetectable after 4 weeks therapy with Tenofovir alafenamide fumarate (TAF). Serum transaminases went down to normal 3 months later after receiving TAF. HBV reactivation is a substantial risk for patients with isolated HBcAb positive receiving rituximab-containing chemotherapy without anti- HBV drug. Regular monitoring with a frequency of 1-3 months is the basis for timely diagnosis and treatment of HBV reactivation. Serum transaminases abnormalities may be the initial manifestation of HBV reactivation.